Incorporation of ion exchange functionalized-montmorillonite into solid lipid nanoparticles with low irritation enhances drug bioavailability for glaucoma treatment - Shuo Liu; Xinyue Han; Hanyu Liu; Yawen Zhao; Huamei Li; Ilva D. Rupenthal; Zhufen Lv; Yanzhong Chen; Fan Yang; Qineng Ping; Yufang Pan; Dongzhi Hou (Taylor & Francis Group, 2020)
Montmorillonite-loaded solid lipid nanoparticles with good biocompatibility, using Betaxolol hydrochloride as model drug, were prepared by the melt-emulsion sonication and low temperature-solidification methods and drug bioavailability was significantly improved in this paper for the first time to application to the eye. The appropriate physical characteristics were showed, such as the mean particle size, Zeta potential, osmotic pressure, pH values, entrapping efficiency (EE%) and drug content (DC%), all showed well suited for possible ocular application. In vitro release experiment indicated that this novel system could continuously release 57.83% drugs within 12 h owing to the dual drug controlled-release effect that was achieved by ion-exchange feature of montmorillonite and structure of solid lipid nanoparticles. Low irritability and good compatibility of nanoparticles were proved by both CAM-TBS test and cytotoxicity experiment. We first discovered from the results of Rose Bengal experiment that the hydrophilicity of the drug-loaded nanoparticles surface was increased during the loading and releasing of the hydrophilic drug, which could contribute to prolong the ocular surface retention time of drug in the biological interface membrane of tear-film/cornea. The results of in vivo pharmacokinetic and pharmacodynamics studies further confirmed that increased hydrophilicity of nanoparticles surface help to improve the bioavailability of the drug and reduce intraocular pressure during administration. The results suggested this novel drug delivery system could be potentially used as an in situ drug controlled-release system for ophthalmic delivery to enhance the bioavailability and efficacy.